Mechanical characterization and thermal investigation of nylon polymer matrix composites used in automotive power train systems - Thillikkani Shanmugam; Manoj Abraham D S; Suresh N; Sathish Obili (Materials Research Express)
Failures may result from a variety of mechanical issues, including the improper composition of the components. This study synthesizes specific typical varying materials, including nylon 6/6 and glass fibers, with unique volume proportions to improve abrasion resistance and extend the lifespan of equipment. The research demonstrated that polymer gears have a lengthier longevity than gears that are entirely composed of nylon. The specimen samples undergo a variety of evaluations, including tensile, compressive, flexural, impact, Thermo Gravimetric analysis, and wear assessments. Nevertheless, the rate of depreciation remains constant. An experiment has been conducted that involves a composite of 90% nylon and 10% nylon with 10% glass fiber. Research indicates that the combination of 10% Nylon 6/6 produces optimistic outcomes. The research indicates that a composition that comprises 30% glass fiber and 70% Nylon 6/6 offers exceptional strength, wear resistance, and reduced wear.